Maintaining spiritual and balance technology in the AI era - Trisia, Riri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Artificial intelligence (AI) technology has brought about profound changes in many facets of human existence, posing new difficulties that have an impact on mental and spiritual equilibrium. With an emphasis on how people might stay connected to spiritual parts of life in the face of rapid change, this study examines the significance of preserving balance between spiritual ideals and technological advancements. To lessen the effects of